Surface rheology: Macro- and microrheology of poly(tert-butyl acrylate) monolayers - Maestro, Armando (2011)
We have studied the surface shear viscoelasticity of poly(tert-butyl- acrylate) Langmuir monolayers spread at the air/water interface, by tracking the Brownian motion of tracer particles with different sizes and surface chemical nature, trapped at the same interface. Surface shear moduli have been extracted from the particles mean square displacements (MSD), using different approaches: hydrodynamic calculations of drag coefficients and direct inversion of the MSD by means of the generalized Stokes-Einstein equation. It has been found that these different theoretical approaches lead to comparable values of the shear interfacial viscosity independent of the polymer concentration and molecular weight. In addition, no effect of the size or chemical nature of the probe has been detected. The results have demonstrated the consistency of the microrheological techniques used, and confirm the existence of entanglements in PtBA monolayers, as recently deduced from dilational elasticity and viscosity measurements, [Maestro et al., Soft Matter, 2010, 6, 4407]. An unexpected result was that the interfacial viscosity values obtained from microrheology have been found to be several orders of magnitude lower than the ones obtained with macroscopic interfacial shear rheometers. At the moment there is no clear explanation for this disagreement, although it is not related to the probe size or their chemical nature. Furthermore, this discrepancy is not related to the analysis methodology used, including the calculation of the two-point correlation function used in 3D microrheology when there are heterogeneities present within the range of the probe size. © The Royal Society of Chemistry 2011.